Perancangan Standard Operating Procedure Medical Treatment untuk Departemen Human Resources di PT. Y - Suseno, Valencia; Halim, Siana (Jurnal Titra, 2014)
Human resources (HR) department is a department in charge of hiring, training, assess, and provide compensation to employees, pay attention to their labor relations, health and safety, and justice isses. Meeting the employeesâ needs, the HR department must have a clear workflow. Therefore the Standard Operating Procedure (SOP) is a necessity to be updated, so that there will be no social gap between the parties. In this work, we updated eight SOPs that have no longer accordance with the aggrement of HR department and its vendors which includes several processes in the HR medical of vendor by vendor N and vendor BL. The SOP for hospital regristration processes was created for Hospital Handover Project such that each group (the east and the west group) can handle those processes individually.